2014
DOI: 10.3109/19396368.2014.967368
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fertilization mode, embryo morphology at day 3, and female age on blastocyst formation and the clinical outcomes

Abstract: (2015) The effects of fertilization mode, embryo morphology at day 3, and female age on blastocyst formation and the clinical outcomes, Systems Biology in Reproductive Medicine, 61:1, 50-56, DOI: 10.3109/19396368.2014 AbstractThe aim of this study was to evaluate the influence of in vitro fertilization (IVF) versus intracytoplasmic sperm injection (ICSI), fertilization mode embryonic morphology at day 3, and female age on blastocyst development, on the clinical outcomes of pregnancy after blastocyst transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…However, there was an important difference compared with our study, in which all embryos vitrified on D5 or D6 were warmed on D5 progesterone and transferred after 2 or 3 h. There is limited information on the reasons why blastocysts with delayed blastulation exert a lower clinical outcome. In addition to metabolic imbalances and bioenergetics issues, higher aneuploidy rates in slow growth embryos have been proposed as a possible explanation (Capalbo et al, 2014;Yin et al, 2015). Taylor et al (2014) calculated that blastocysts that formed and were vitrified on D6 (slow developing embryos) had a 10% increase in aneuploidy rates compared with those that formed on D5, and this difference might be the reason for their lower pregnancy outcome after vitrified-warmed transfer.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was an important difference compared with our study, in which all embryos vitrified on D5 or D6 were warmed on D5 progesterone and transferred after 2 or 3 h. There is limited information on the reasons why blastocysts with delayed blastulation exert a lower clinical outcome. In addition to metabolic imbalances and bioenergetics issues, higher aneuploidy rates in slow growth embryos have been proposed as a possible explanation (Capalbo et al, 2014;Yin et al, 2015). Taylor et al (2014) calculated that blastocysts that formed and were vitrified on D6 (slow developing embryos) had a 10% increase in aneuploidy rates compared with those that formed on D5, and this difference might be the reason for their lower pregnancy outcome after vitrified-warmed transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Higher implantation and pregnancy rates allow the transfer of a single blastocyst to reduce the risk of multiple gestations [5,21]. Meanwhile, the top day-3 embryos also have an optimistic pregnancy rate [8]. It has been reported that day-3 embryo transfers with more than two eight-cell-stage embryos and less than 20% fragmentation appear to have a similar implantation rate as the blastocyst transfers [23], and blastocysts do not improve the cumulative pregnancy rate [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Although embryo evaluation criteria can help us select embryos [4], scholars have further claimed that the implantation rate and pregnancy rate for blastocysts are higher than those for embryos, indicating that blastocyst transfer is more advantageous than day-3 embryo transfer, particularly for high-quality blastocysts [5,6]. It has also been reported that a good day-3 embryo is apt to form a high-quality blastocyst [7,8]. However, not all good day-3 embryos can form high-quality blastocysts, partly because of the negative effect of being exposed to in vitro conditions for a long time [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on reduced pregnancy outcomes from transferring embryos with poor morphology [29,30]. Some embryo dysmorphisms, however, like cytoplasmic fragments and coarse granulation in PVS, could be removed from to degeneration or lysis of healthy neighboring blastomeres [14].…”
Section: Discussionmentioning
confidence: 99%